Rhizophoraceae alkaloids : studies in the synthesis of Gerrardine - Kleynhans, Carl Rudolf (Department of Chemistry, 2016)
Gerrardine, an alkaloid isolated from Cassipourea gerrardii was previously established as 1-methyl-2,5-bis( 4'-hydroxy-1',2'-dithiolan-3'-yl)-pyrrolidine. The aim of the present research was to study the ways in which 1-methyl-2-(4'-hydroxy-1', 2'-dithiolan-3'-yl)-pyrrolidine, as a model compound could be synthesised since it contained asymmetric centres corresponding to those of gerrardine. The work resolved itself into attempts at the synthesis of 3-(1'-methylpyrrolidin-2'-yl)-1,3-dithiolpropan-2-ol since this would be converted into the required dithiolane by mild oxidation.